Conical-intersection quantum dynamics of OH(A2?+) + H(2S) collisions - Gamallo, Pablo; Akpinar, Sinan; Defazio, Paolo; Petrongolo, Carlo (Amer Inst Physics, 2013)
We present the conical-intersection quantum dynamics of the nonreactive quenching (NQ) OH(A(2)Sigma(+)) + H'(S-2) -> OH(X-2 Pi) + H'(S-2), exchange (X) OH(A(2)Sigma(+)) + H'(S-2) -> OH'(A(2)Sigma(+)) + H(S-2), exchange-quenching (XQ) OH(A(2)Sigma(+)) + H'(S-2) -> OH'(X-2 Pi) + H(S-2), and reaction (R) OH(A(2)Sigma(+)) + H'(S-2) -> O(D-1) + H-2(X-1 Sigma(+)(g)) collisions. We obtain initial-state-resolved reaction probabilities, cross sections, and rate constants by considering OH in the ground vibrational state and in the rotational levels j(0) = 0, 1, 2, and 5. Coupled-channel real wavepackets (WPs) on the (X) over tilde (1) A' and (B) over tilde (1) A' coupled electronic states are propagated by using the Dobbyn and Knowles diabatic potential surfaces and coupling [A. J. Dobbyn and P. J. Knowles, Mol. Phys. 91, 1107 (1997) and A. J. Dobbyn and P. J. Knowles, Faraday Discuss. 110, 207 (1998)], and performing asymptotic or flux analysis. NQ is the preferred product channel, followed by XQ, R, and X. Moreover, the nonadiabatic quenching processes account for more than 80% of the total rate constants. WP snapshots show a reaction mechanism in good agreement with reaction probabilities. NQ, XQ, and R cross sections, and NQ rate constants decrease with the collision energy and j0, whereas the X reactivity increases, and XQ and R rates are nearly constant with j0. In general, quantum rate constants are smaller than experimental or quasiclassical data. (C) 2013 AIP Publishing LLC.
Keywords: Reactive Scattering Calculations; Real Wave-Packets; Atomic-Hydrogen; Cross-Section; H-Atoms; State; H-2; Relaxation; Collisions; Surface